Routledge handbook on the Kurds - Gunter, Michael M. (Routledge handbooks, 2019)
Part 1. Kurdish studies. Kurdish studies in the United States / Michael M. Gunter ; Kurdish studies in Europe / Vera Eccarius-Kelly -- Part 2. Early Kurdish history. The Kurdish Emirates ; obstacles or precursors to Kurdish nationalism? / Michael Eppel ; An overview of Kurdistan of the 19th century / Hamit Bozarslan ; The development of the Kurdish national movement in Turkey from Mahmud II to Mustafa Kemal Ataturk Serdar Akturk -- Kurdish culture. Ehmede Khani's Mem u zin : the consecration of a Kurdish national epic / Michiel Leezenberg -- Classical and modern Kurdish literature / Hashem Ahmadzadeh ; Calibrating Kurmanji and Sorani : proposal for a methodology / Michael L. Chyet ; Kurdish cinema / Bahar Simsek -- Economic dimensions. The oil imperative inthe KRG / David Romano ; De-development in eastern and southeastern Anatolia / Veli Yadirgi -- Part 5. Religion. Islam and the Kurds / Mehmet Gurses ; The inadequate Islamic grappling with the Kurdish issue / Christopher Houston ; The Jewish communities in Kurdistan within the tribal Kurdish society / Mordechai Zaken ; Yezidi baptism and rebaptism : resilience, reintegration, and religious adaptation / Tyler Fisher and Nahro Zagros -- Part 6. Geography and travel. The geopolitics of the Kurds since the first World War : between Iraq and other hard places / Michael B. Bishku ; Roaming Iraqi Kurdistan / Stafford Clarry -- Part 7. Women. Kurdish women / Anna Grabole-Celiker -- Part 8. The Kurdish situation in Turkey. The rise of the pro-Kurdish democratic movement in Turkey / Cengiz Gunes ; The Kurdistan Workers Party (PKK) and Kurdish political parties in the 1970s / Joost Jongerden and Ahmet Hamdi Akkaya ; Turkey's Kurdish complexes and Its Syrian quagmire / Bill Park -- Part 9. The Kurdish situation in Iraq. The State We're in: Post-Colonial Sequestration and the Kurdish Quest for Independence since the First World War / Francis Owtram ; The disputed territories of Northern Iraq : ISIS and beyond / Liam Anderson ; The continuing problem of KRG corruption / Michael Rubin ; The Russian historical and political approach towards non-conventional independence of Iraqi Kurdistan / Kirill V. Vertyaev -- Part 10. The Kurdish situation in Syria. The Kurdish PYD and the Syrian Civil War / Eva Savelsberg ; The Evolution of the Kurdish struggle in Syria : between pan-Kurdism and Syrianization, 1920-2016 / Jordi Tejel ; The roots of democratic autonomy in Northern Syria / Rojava Michael Knapp -- PART 11. Iran. Iran and the Kurds / Nader Entessar -- Part 12. The Kurdish diaspora. The future of the Kurdish diaspora / Osten Wahlbeck ; Diasporic conceptions of the Kurdistan Region of Iraq / Barzoo Eliassi ; The Kurds in Germany / Vera Eccarius-Kelly ; The Kurdish diaspora in the UK / Desmond Fernandes